Rural-urban differences in physical activity and TV-viewing in Brazil - Andrea Wendt; Adriana Machado; Caroline Costa; Cauane Blumenberg; Luiza Ricardo; Rafaela Martins; Gregore Mielke (James Cook University, 2022)
Introduction: This study aims to compare differences regarding physical activity (PA) indicators and TV viewing according to location of residence and sociodemographic variables in Brazil. Methods: This cross-sectional study with individuals aged 18 years or older using data from the Brazilian National Health Survey was carried out in 2013. PA (total and domains) and TV viewing (≥3 hours) were measured by self-report. Stratifiers were location of residence, sex, age, wealth quintiles and regions of the country. Results: This study included 60 202 individuals (49 245 from urban areas). In general, total PA was not different according to location of residence (urban 59.4%; rural 57.4%). Higher differences were found for leisure-time PA (urban 24.1%; rural 13.9%), work-based PA (urban 12.9%; rural 21.1%) and TV viewing of more than 3 hours (urban 30.1%; rural 21.4%). The differences between urban and rural areas were enhanced according to sex, age and wealth quintiles. Conclusion: The differences between urban and rural areas vary according to PA domains and population groups. To explore specific domains of PA in each location of residence may improve the understanding of the analyzed outcomes in different communities and consequently guide future interventions.